Introduction to coordination, solid state, and descriptive inorganic chemistry - Rodgers, Glen E. ([S.l.] : Mcgraw-Hill College, 1994)
This book is an introduction to coordination, solid state, and descriptive inorganic chemistry. It is designed primarily for an undergraduate inorganic chemistry audience but could also be used as a supplementary text for some general chemistry courses and as a reference book for teachers of chemistry at all levels. This book offers the following features: it is designed for the increasingly popular sophomore-level inorganic course; it is presented in three modules to allow for flexibility in teaching; it contains over 900 end-of-chapter problems of varying levels of difficulty and full explanatory answers test students' critical thinking skills; and it offers numerous real world applications including environmental, energy-related and medical issues.
Keywords: chemistry,inorganic chemistry